2021
DOI: 10.48550/arxiv.2110.08728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On universally optimal lattice phase transitions and energy minimizers of completely monotone potentials

Senping Luo,
Juncheng Wei,
Wenming Zou

Abstract: We consider the minimizing problem for energy functionals with two types of competing particles and completely monotone potential on a lattice. We prove that the minima of sum of two completely monotone functions among lattices is located exactly on a special curve which is part of the boundary of the fundamental region. We also establish a universal result for square lattice being the optimal in certain interval, which is surprising. Our result establishes the hexagonal-rhombic-square-rectangular transition l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In [23] we have considered the following minimization problem of sum of two theta functions min z∈H θ(α; z) + ρθ(α; z + 1 2 ) (1.4) and showed that the hexagonal-rhombic-square-rectangular transition appears as ρ goes from 0 to +∞. This result can also be generalized to completely monotone functions.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%
“…In [23] we have considered the following minimization problem of sum of two theta functions min z∈H θ(α; z) + ρθ(α; z + 1 2 ) (1.4) and showed that the hexagonal-rhombic-square-rectangular transition appears as ρ goes from 0 to +∞. This result can also be generalized to completely monotone functions.…”
Section: Introduction and Statement Of Main Resultsmentioning
confidence: 99%